VD_FINDINFO HC / 2016 / 118 vom 25. Januar 2016 - VD Tribunal cantonal (2016)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, MESURE PROVISIONNELLE, APPRÉCIATION DES PREUVES | 176 al. 1 ch. 1 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)